SCREENING FOR DYSLIPIDEMIA AND EXPEDIENCE OF STATIN THERAPY FOR THE CITIZENS OF TRANSCARPATHIA VALLEY REGIONS WITH OVERWEIGHT AND OBESITY - Kedyk, A. V.; Rishko, M. V.; Kutsyn, O. O. (International Journal of Medicine and Medical Research, 2017)
Background. The lipid profiles of patients with overweight, obesity and healthy individuals, the citizens of Transcarpathia valley regions were analysed. Objective. The study was aimed at evaluation of dyslipidaemia frequency in patients with overweight and obesity, determination of expedience of statins prescription. Methods. All patients were divided into 2 groups: group 1 – patients with overweight; group 2 – patients with obesity of I and II degree. Estimation of lipid profile parameters was conducted by means of spectrophotometric device SIEMENS Dimension RxL Max. Statistical analysis of the data was conducted using Microsoft Excel 2007. Results. The patients with obesity had higher level of total cholesterol (6.03±0.53 mmol/l), lower HDL-C (1.15±0.07 mmol/l) and higher level of LDL-C (4.19±0.46 mmol/l) compare with overweight patients. In 46% of patients with overweight, dyslipidaemia was evidenced and required correction, 27% of them had high CVR and needed statin therapy, 19% of people with obesity had moderate CVR and didn’t need statins. 77% of obese patients needed lipid correction, 54% of them with very high and averagely high level of CVR required statin therapy; 23% of people with obesity had moderate CVR and did not need statins. Conclusions. In the studied overweight and obese patients, atherogenic dyslipidaemia was established in 46% and 77% of cases respectively. Correction of dyslipidaemia with statin was compulsory for 27% of patients with overweight and for 54% with obesity.